2019
DOI: 10.1088/1755-1315/272/2/022124
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Qualitative Chemical Composition of Technogenic Waters in the Tailing Dumps of the Russian Southern Far East in a Wide Temperature Range Using the Physicochemical Modeling Method

Abstract: The article presents the results of technogenic waters composition physicochemical modeling for Kavalerovsky and Dalnegorsk ore districts closed tailing dams (Primorsky Krai, South of the Russian Far East). Thermodynamic modeling in “Selektor” software package in a wide temperature range from -10 to +30 °C allowed to establish the Eh-pH characteristics and to study quantitative and qualitative composition of slurry and drainage waters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…The calculations of technogenic waters (sludge and drainage) modeling included 19 independent (Al, Ar, As, B, C, Ca, Cu, Fe, K, Mg, N, Na, Pb, S, Si, Zn, H, O, andē) and 371 dependent components: 283 dissolved particles, 18 gases, and 70 solid phases. The obtained results were partly published in works [16,[18][19][20][21][22][23][24][25][26][27]. Modeling showed that most of the hypergenic minerals (Table 1) crystallize from highly concentrated solutions in the temperature range from −25 to 45 • C.…”
Section: Crystallization From Tailings Dumps Sludge and Drainagementioning
confidence: 87%
“…The calculations of technogenic waters (sludge and drainage) modeling included 19 independent (Al, Ar, As, B, C, Ca, Cu, Fe, K, Mg, N, Na, Pb, S, Si, Zn, H, O, andē) and 371 dependent components: 283 dissolved particles, 18 gases, and 70 solid phases. The obtained results were partly published in works [16,[18][19][20][21][22][23][24][25][26][27]. Modeling showed that most of the hypergenic minerals (Table 1) crystallize from highly concentrated solutions in the temperature range from −25 to 45 • C.…”
Section: Crystallization From Tailings Dumps Sludge and Drainagementioning
confidence: 87%
“…Необходимо отметить, что процессы гипергенеза в горнопромышленных техногенных системах оказывают наибольший уровень негативного воздействия именно на компоненты гидросферы. Следствием разгрузки техногенных вод (дренажа рудников, шламовых и дренажных вод хвостохранилищ, а также прудков-отстойников) в поверхностные и подземные природные водные объекты становится их загрязнение как по всему миру [2][3][4][5][6], так и в рассматриваемых районах [7][8][9][10][11][12], что повышает риски для здоровья населения [13][14][15].…”
unclassified
“…Следует отметить гидрохимические исследования и в рассматриваемом горнорудном районе [16][17][18][19]. Разными авторами установлено увеличение значений канцерогенных и неканцерогенных рисков здоровью населения при различных сценариях экспозиции загрязняющих веществ в воде [20][21][22][23][24][25].…”
unclassified